2015
DOI: 10.1534/genetics.115.175596
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Changes in Gimap3 and Gimap5 Expression Modify Mitochondrial DNA Segregation in Mice

Abstract: Mammalian mitochondrial DNA (mtDNA) is a high-copy maternally inherited genome essential for aerobic energy metabolism. Mutations in mtDNA can lead to heteroplasmy, the co-occurence of two different mtDNA variants in the same cell, which can segregate in a tissue-specific manner affecting the onset and severity of mitochondrial dysfunction. To investigate mechanisms regulating mtDNA segregation we use a heteroplasmic mouse model with two polymorphic neutral mtDNA haplotypes (NZB and BALB) that displays tissue-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Mechanistic studies in vitro reveal that impairment of GIMAP5-deficient TH cell differentiation is associated with increased DNA damage, which could be controlled by TGF-βin GIMAP5-deficient CD4+ T cells to induce TH17 polarization [ 15 ]. Previous in vivo study showed that GIMAP3/5 modified mitochondrial DNA in a heteroplasmic mouse model [ 16 ], which was consistent with our findings that GIMAPs family members influenced DNA metabolism in either mitochondria or nucleus.…”
Section: Discussionsupporting
confidence: 93%
“…Mechanistic studies in vitro reveal that impairment of GIMAP5-deficient TH cell differentiation is associated with increased DNA damage, which could be controlled by TGF-βin GIMAP5-deficient CD4+ T cells to induce TH17 polarization [ 15 ]. Previous in vivo study showed that GIMAP3/5 modified mitochondrial DNA in a heteroplasmic mouse model [ 16 ], which was consistent with our findings that GIMAPs family members influenced DNA metabolism in either mitochondria or nucleus.…”
Section: Discussionsupporting
confidence: 93%
“…Among the 118 single mitochondrion samples from mice, there were on average 3.9 SNV sites per mitochondrion with a standard deviation of 5.71, indicating over-dispersion of SNV sites with some mitochondrion containing an unexpected high or low mutational load. Such over-dispersion might arise from preferential birth-death of certain multi-loci variant combinations leading to fitness effects (cf., Jokinen et al, 2015. ; Jenuth et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…We note several complicating factors may influence our results including unusual cellular environment within in vitro cell cultures leading to de novo mutations as well as possible effects of somatic selection which may depend on variation at other genomic loci or tissue specific selection (e.g., Jokinen et al, 2015; Jenuth et al, 1997). Unusual environment leading to mutations can influence the total number of SNV loci but we believe it unlikely to lead to SNVs shared in multiple samples as those described in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…In the same NZB/BALBc model, Jokinen et al . () studied the preferential selection for BALBc mtDNA in hematopoietic cells and found that the tail‐anchored, ER‐resident GTPases Gimap3 and Gimap5 play a critical role in mtDNA segregation, suggesting that coordination of organelle interactions may be involved in modulating mtDNA segregation and selection.…”
Section: Proposed Mechanisms By Which Purifying Selection May Occurmentioning
confidence: 99%